EFFICIENCY OF THE PROCESS OF BALANCED LAND USE UNDER MARTIAL LAW - Iryna Bodnaruk (Izdevnieciba "Baltija Publishing", 2024)
The article discusses the process of balanced land use and its efficiency, which is an extremely important element of socio-economic development of any country. Since land is Ukraine's main natural resource, the basis of life and a source of income, the efficiency of using this potential is not being realised to the fullest extent in the current environment. For more than two years now, Ukraine has been under constant shelling and land seizures, so the need to improve the level of land protection is urgent and, given the difficult conditions of hostilities, is becoming a top priority. The purpose of this article is to analyse the functioning of the land market and highlight the main changes and problems that have arisen in the course of the land reform. Methodology. For this purpose, both general scientific and special methods of cognition of phenomena were used: analysis, synthesis, selection and generalisation. Results. This allowed to identify the relevant tasks, which are to create fundamental conditions and rights for all users to dispose of the land fund, as well as to ensure compliance with the responsibility for improper use. This may become an important prerequisite for introducing new effective ways to address and improve the process of balanced land use. The revision of the existing legal framework for regulating the land market after the lifting of the moratorium on the sale of agricultural land, especially in the context of military operations in Ukraine, has helped to ensure, first and foremost, the protection and guarantee of property rights. Practical implications. The relevance of this paper lies in the implementation and formation of a land policy that will primarily ensure the development and functioning of the land market in the system of balanced land use, both today and in the near future. Value/Originality. The proposed new mechanisms for establishing land relations in a market environment will help to increase the efficiency of land use and the value of land resources, which should be extremely important for the growth of the full economic potential of the state and strengthening the position of Ukraine as a guarantor of global food security.